Introduction to supply chain management technologies - Ross, David Frederick, 1948- (Series on resource management., 2011)
The second edition of this popular resource reflects new technology in supply chain management. Providing a comprehensive review of business computing, it features new chapters on the fundamentals of computing and their enabling power as well as the basics of contemporary ERP/supply chain business solutions. This book remains a critical resource on the enabling power of today's technologies and their impact on supply chain management. Focusing on the impact of the Internet on strategic elements of supply chain management, the author highlights integrative software tools that allow for new leve.